The Impact of Digital Literacy, Accessibility, and Service Quality on User Satisfaction of PANDAWA BPJS Health Services - Nisa, Nur; Akib, Haedar; Niswaty, Risma; H, Herman (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the impact of Digital Literacy, Accessibility, and Service Quality on User Satisfaction of PANDAWA BPJS Kesehatan in Makassar City. The research involved 100 respondents, ranging from 19 to 58 years old, with a majority being from Tamalate and Rappocini. The validity of the questionnaire showed a significant correlation between the variables X1, X2, X3, and Y, with Pearson's correlation coefficient of 0.6. The reliability of the questionnaire was also high, with a Cronbach's Alpha of 0.980, indicating good internal consistency. The clausical assumption showed that the questionnaire was multicollinear and heteroscedasticity, but normality was not. The regression analysis showed that variables X2 and X3 significantly influenced the effectiveness of the questionnaire, with a p-value of 0.05. However, variable Xl did not significantly influence the questionnaire. The descriptive analysis revealed that 79.8% of the variance in the questionnaire was explained by digital literacy, accessibility, and service quality, with the model being effective in explaining the relationship between variables XI, X2, X3 and Y. The study concludes that digital literacy does not significantly influence the effectiveness of PANDAWA BPJS Kesehatan in Makassar.